CNP-miR146a Decreases Inflammation in Murine Acute Infectious Lung Injury - Alyssa E. Vaughn; Tanner Lehmann; Christina Sul; Alison M. Wallbank; Bailey D. Lyttle; James Bardill; Nana Burns; Anisha Apte; Eva S. Nozik; Bradford Smith; Christine U. Vohwinkel; Carlos Zgheib; et al. (MDPI AG, 2023)
Acute respiratory distress syndrome (ARDS) has approximately 40% in-hospital mortality, and treatment is limited to supportive care. Pneumonia is the underlying etiology in many cases with unrestrained inflammation central to the pathophysiology. We have previously shown that CNP-miR146a, a radical scavenging cerium oxide nanoparticle (CNP) conjugated to the anti-inflammatory microRNA(miR)-146a, reduces bleomycin- and endotoxin-induced acute lung injury (ALI) by decreasing inflammation. We therefore hypothesized that CNP-miR146a would decrease inflammation in murine infectious ALI. Mice were injured with intratracheal (IT) MRSA or saline followed by treatment with IT CNP-miR146a or saline control. Twenty-four hours post-infection, bronchoalveolar lavage fluid (BALF) and whole lungs were analyzed for various markers of inflammation. Compared to controls, MRSA infection significantly increased proinflammatory gene expression (IL-6, IL-8, TNFα, IL-1β; p < 0.05), BALF proinflammatory cytokines (IL-6, IL-8, TNFα, IL-1β; p < 0.01), and inflammatory cell infiltrate (p = 0.03). CNP-miR146a treatment significantly decreased proinflammatory gene expression (IL-6, IL-8, TNFα, IL-1β; p < 0.05), bronchoalveolar proinflammatory protein leak (IL-6, IL-8, TNFα; p < 0.05), and inflammatory infiltrate (p = 0.01). CNP-miR146a decreases inflammation and improves alveolar-capillary barrier integrity in the MRSA-infected lung and has significant promise as a potential therapeutic for ARDS.